Comparative efficiency of insecticides and application methods to control pineapple-mealybugs - Cecília, Lenira Viana Costa Santa; Rossi, Marta Maria (Pesquisa Agropecuaria Brasileira, 1991)
A field experiment conducted in Monte Alegre de Minas, MG, Brazil, was used to compare the efficiency of diazinon and methidathion in different application methods, to control pineapple-mealybugs, Dysmicoccus brevipes (Cockerell, 1893) (Homoptera: Pseudococcidae). The treatments were: treatment of pineapple cuttings with diazinon or methidathion; field spray of either insecticide; treatment of cuttings followed by spray in the field using either insecticide, two conventional chemical control methods and a control treatment. The results showed that all chemical treatments were efficient to control pineapple mealybugs. The cutting treatments should be used once this technique gave a long-term control for ten months.